Penataan Administrasi GKI Maleo melalui Pendampingan Pengembangan Website Data Keanggotaan: Pengabdian - Singadji, Marcello; Hulu, Dalizanolo; Siregar, Johannes Hamonangan; Sadira, Aundrel Aza; Abarua, Nathasa Rowen Frederika; Makarena, Maria Rachel Kesya; Christy, Tegar Surya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Membership administration is a fundamental component of effective church governance. GKI Maleo faces challenges in managing congregational data due to the continued use of manual record-keeping systems, which leads to risks of data loss, duplicated information, and difficulties in data management. This community service activity aims to assist GKI Maleo in reorganizing its membership administration through the development of a membership data website that includes features for personal data, family information, sacramental records, membership transfers, and service history. The implementation method includes needs analysis, system design, website development, user training, as well as monitoring and evaluation. The results show a significant improvement in data accuracy, efficiency in data retrieval, and the church administrators’ ability to manage congregational information digitally. The development of this website provides a tangible contribution to the modernization of church administration and enhances the quality of services provided to the congregation.